Unilateral frontal lobectomy can produce strategy application disorder. Issue 3 (March 1993) - Goldstein, L H; Bernard, S; Fenwick, P B; Burgess, P W; McNeil, J
Abstract : Following a 5 cm left frontal lobectomy for the removal of a mixed astrocytoma-oligodendroglioma, a 51 year old right handed man showed a marked dissociation between his performance on standard neuropsychological tests and his everyday behaviour. In contrast to his intact neuropsychological test performance, he was impaired on a test of "strategy application" which requires goal articulation, plan specification, self-monitoring, and evaluation of outcomes, as well as the establishment of mental "markers" to trigger specific behaviour. Strategy application disorder can therefore be produced by a unilateral circumscribed frontal lobe lesions.